Choosing outcome indicators of household food security: Technical Guide: Strengthening the household food security and nutritional aspects of IFAD poverty alleviation projects: developing operational methodologies for project design and monitoring - Hoddinott, John F. (International Food Policy Research Institute, 1999)
Many development agencies regard the concept of household food security—often defined as adequate access to food at all times, throughout the year and from year to year—as a guiding principle for designing interventions in rural areas. A commitment to household food security carries with it an important implication for development practitioners, namely the need to measure food security outcomes at the household and individual level.1 Measurement is necessary at the outset of any development project to identify the food insecure, to assess the severity of their food shortfall and to characterize the nature of their insecurity (seasonal versus chronic). Further, it provides the basis for monitoring progress and assessing the impact of these projects on the beneficiaries' food security.